Annual International Convention of the Rosicrucian Order A.M.O.R.C. - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of members of the Rosicrucian Order, Ancient and Mystical Order Rosae Crucis, at the Egyptian Rosicrucian Museum. The attendees include men, women and children wearing convention badges.